Cross-sectional flexural capacity of cold-formed laterally-restrained steel rectangular hollow flange beams - Tondini, Nicola; Morbioli, Andrea (Thin-walled structures, 2015)
This paper presents the results of a comprehensive experimental-numerical study aimed at determining the flexural performance of cold-formed laterally-restrained steel rectangular hollow flange beams (RHFBs). Two RHFBs of different dimensions were considered as representative of typical secondary beams in small steel-framed houses. Results of the experimental study that consisted of (i) material characterisation and (ii) tests on full-scale specimens are thoroughly presented. Moreover, a numerical work was performed in order to develop a model able to reproduce the experimental outcomes and used to expand the available findings over a wider slenderness range through parametric studies. •Complete experimental analysis of the bending capacity of cold-formed steel profiles.•Tests on rectangular hollow flange I symmetric sections.•Favourable flexural performance/weight ratio for structural applications as secondary beams.•Good agreement between numerical and experimental results.•EN1993 and Direct Strength Method predictions are on the safe side.